Effect of addition of dendritic C60 amphiphiles on the structure of cationic surfactant solutions - Li, Hongguang; Liu, Changcheng; Hao, Jingcheng; Hirsch, Andreas (Journal of Colloid and Interface Science, 2008)
The aggregation behavior of two water-soluble carboxylic C derivatives, dendritic methano[60] fullerene octadeca acid (1) and ennea acid (2), in aqueous solutions was investigated. Both 1 and 2 were highly soluble in pure water and buffer solutions with pH ≥7.0. Their spectral properties, especially those in the visible region, were found to be influenced greatly by solution parameters and additives. In pure water, dynamic laser light scattering (DLS) measurements revealed that both 1 and 2 could form aggregates. When 1 or 2 was added to micelle solution of a cationic surfactant, tetradecyltrimethylammonium hydroxide (TTAOH), unilamellar vesicles with diameters of several hundreds of nanometers were detected by freeze-fracture transmission electron microscope and DLS both below and above the critical micellar concentration of TTAOH. Vesicle formation was greatly suppressed when 1 or 2 was added to tetradecyltrimethylammonium bromide micelle solution and no vesicles were detected for 1 or 2 mixed with the aqueous solutions of tetrabutylammonium hydroxide or tetramethylammonium hydroxide, indicating that counterions and the hydrophobic chain length of the cationic surfactants played important roles in vesicle formation. At the same time, for mixtures of 1 and 2 with anionic surfactant sodium dodecyl sulfate, no vesicles were detected. In highly concentrated NaCl solutions, it was found that 1 and 2 could also form vesicles, which could be due to the shielding of the electrostatic interactions among hydrophilic parts of 1 and 2. © 2007 Elsevier Inc. All rights reserved.